“I’VE READ YOU RIGHT—I’M WITH YOU NOW”: AESTHETIC READING IN VIRGINIA WOOLF'S METAFICTIONAL SHORT STORIES - Paris-Popa, Andreea (Studia Universitatis Babeș-Bolyai. Philologia, 2024)
“I’ve read you right—I’m with you now”: Aesthetic Reading in Virginia Woolf’s Metafictional Short Stories. Despite critical interest in Virginia Woolf’s intense preoccupation with the imaginative process at the root of literary creation, little attention has been paid to the manner in which, through metafiction, the writer turns her short stories into reflections upon the nature of reading. In works such as “An Unwritten Novel” (1921) and “The Lady in the Looking-Glass. A Reflection” (1926), the boundaries between literature and criticism, between fiction and reality, take center stage and it is precisely this point of convergence that metafictional works take as subject matter. Thus, Virginia Woolf’s ‘character-reading’ makes its way into her stories and the author’s critical stance upon the act of reading, revealed primarily in her essays, is now transmitted thematically through characters who appropriate the readers’ active construction of meaning while living in the same textual world inhabited by the fictitious characters they ardently wish to interpret. Through the advancement of a specific type of reading: active, emotive, empathetic, fluid, inquisitive, intimate and indeterminate, yet always close to the text it is engaged with, Virginia Woolf may be said to prefigure the type of transactional reader-response criticism underpinned by Louise Rosenblatt, whose insistence upon aesthetic reading calls for a two-way transmission of meaning that is simultaneously constitutive of the literary work and of the reader’s self.